FORMATION OF LOPSIDED AND BAR STRUCTURES IN NON-STATIONARY GRAVITATING SYSTEMS. I- ISOTROPIC CASE - Sultana, M.; Khalid, M. (The Nucleus, 2013)
This is an examination of the gravitational instability of bar-like and lopsided structures of non-stationary isotropic disk model. Non-stationary analogs of the dispersion equation of these two oscillation modes are discussed, in this paper. Growth rates of both oscillation modes are found with the help of non-stationary dispersion equation. Results are presented in the form of graphs which show dependence of initial virial ratio on rotation parameter . A comparative analysis of the growth rates of both oscillation modes is made and found that lopsided structures overall dominates the bar-like structures.